2021
DOI: 10.1186/s13099-021-00438-0
|View full text |Cite
|
Sign up to set email alerts
|

The penicillin binding protein 1A of Helicobacter pylori, its amoxicillin binding site and access routes

Abstract: Background Amoxicillin-resistant H. pylori strains are increasing worldwide. To explore the potential resistance mechanisms involved, the 3D structure modeling and access tunnel prediction for penicillin-binding proteins (PBP1A) was performed, based on the Streptococcus pneumoniae, PBP 3D structure. Molecular covalent docking was used to determine the interactions between amoxicillin (AMX) and PBP1A. Results The AMX-Ser368 covalent complex interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In this study, none of the previously validated amino acid variants linked to amoxicillin, namely S402G, S414R, V469M, S543R, T556S and N561Y was found in our study [19,23]. This observation was in agreement with the published surveillance data on the primary resistance of H. pylori in Malaysia, which consistently reported a 0 % resistance rate [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, none of the previously validated amino acid variants linked to amoxicillin, namely S402G, S414R, V469M, S543R, T556S and N561Y was found in our study [19,23]. This observation was in agreement with the published surveillance data on the primary resistance of H. pylori in Malaysia, which consistently reported a 0 % resistance rate [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 92%
“…The transformant carried V469M and F473L showed increased resistance in MIC value for amoxicillin to 1.0 µg ml −1 which was identical to that of amoxicillin-resistant clinical isolate B258 [22]. Apart from that, new mutations in the pbp1A gene were reported in H. pylori isolates from Vietnam, Iran, Taiwan and Myanmar, however their association with resistance still awaits confirmation [11, 19, 27, 28].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Studies observed that phenotypic AMX resistance is mainly related to mutations that alter the protein encoded by the penicillin-binding protein pbp1A gene [ 18 ] Mutations in pbp1a have been found in three countries. Interestingly, the novel mutations found in each country are diverse.…”
Section: Identification Of Well-known and Novel Resistancesmentioning
confidence: 99%
“…Moreover, H. pylori can be associated with some non-gastric diseases, such as cardiovascular, respiratory, neurologic, hematologic, dermatologic and allergic disorders ( Gravina et al, 2018 ; Attaran et al, 2021 ). As one example, it was discovered that there was a correlation between H. pylori infection and problems in the digestive tract, such as abdominal pain and diarrhea in Coronavirus disease of 2019 (COVID-19) patients ( Balamtekin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%